A Computational Approach for Better Classification of Breast Cancer using GeneticAlgorithm (International Journal of Engineering and Computer Science, 2015)
The proposed work presents a competent diagnosis technique in classifying benign and malignant breast cancer cases using Genetic Algorithm. The breast cancer dataset (Wisconsin Breast Cancer (WBC)) was taken fromUCI Machine Learning Repository, center for machine learning and intelligence systems. Using the proposed Genetic algorithmbased on 3-fold cross validation method, and executing on multiple rules, we obtained preeminent classification accuracy of 97.7% which classified more accurately when compared with the other existing systems. The experimental outcomesillustrate that the categorization using genetic algorithm is loftier to the other classifiers which used WBC dataset. All experiments are carried out on MATLAB.